Respuesta :

Space

Answer:

f(x + 3) = -x² - 8x - 13

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation
  • Expanding
  • Terms/Coefficients/Degrees

Step-by-step explanation:

Step 1: Define

f(x) = -x² - 2x + 2

f(x + 3) is x = x + 3

Step 2: Find

  1. Substitute in x:                    f(x + 3) = -(x + 3)² - 2(x + 3) + 2
  2. Expand:                               f(x + 3) = -(x² + 6x + 9) - 2x - 6 + 2
  3. Distribute -1:                        f(x + 3) = -x² - 6x - 9 - 2x - 6 + 2
  4. Combine like terms:           f(x + 3) = -x² - 8x - 13
ACCESS MORE